(Un)concealing Inequality in the United States Polity - Grgas-Mufa, Stipe (2012)
The presentation argued that the present moment foregrounds the economy in our understanding of the US. Focusing on the growing inequality of US society I took this phenomenon as a barometer by which we can speak of the health of the US polity.
Projekt MZOS
ENG